Exploring Teacher Difficulties and Strategies in Teaching English at Islamic Boarding School of Nurmanisy Hikmatusallam - Saputra, Ogie Winas; Fatimah, Sitti (Journal of English Language Teaching, 2024)
This study aims to understand the teacher's difficulties and strategies in teaching English at Islamic boarding school of Nurmanisy Hikmatusallam which are influenced by the environment and regulations that applied to Islamic boarding school. The design of this research is case study, while the research method used is qualitative. The participants in this research are three English teachers in Islamic Boarding School of NurmanisyHikmatusallam. The data were obtained from two technique, class observation and interview. The results showed that there three challenges faced by the teacher. First, the lack of students’ speaking skill. Based on interview it was found that the reason for student lack of ability in speaking English is that they have never learned English before. Second, the lack of training given to English teachers. It is difficult for teachers to provide students with integrates Islamic value to the English material. Last, the lack of teaching media and school facilities. When teaching English in the class, English teachers use teaching strategies. There are three strategies used by the teachers: inquiry learning, role play, direct instruction.